upper text bottom text left text right text this is for min word req problem in picture
![upper text bottom text left text right text this is for min word req problem in picture class=](https://us-static.z-dn.net/files/d12/49a1c2c98747423e53b4d210d30e3b33.png)
Replace x in the second equation with the value of x from the first one.
x = -3y
x + y = -6
-3y + y = -6
Simplify:
-2y = -6
Divide both sides by -2:
y = -6 / -2
y = 3
Now replace Y with 3 in one of the equations to solve for x:
x = -3y = -3(3) = -9
X = -9, Y = 3
(-9,3)